2016
DOI: 10.3109/14767058.2016.1140734
|View full text |Cite
|
Sign up to set email alerts
|

The common vaginal commensal bacterium Ureaplasma parvum is associated with chorioamnionitis in extreme preterm labor

Abstract: Objective: To assess the association of vaginal commensal and low grade pathogenic bacteria including Ureaplasma parvum, Ureaplasma urealyticum, Mycoplasma hominis, Mycoplasma genitalium, Group B Streptococcus (GBS), and Gardnerella vaginalis, in women who delivered preterm at less than 37 weeks gestation in the presence or absence of inflammation of the chorioamnionitic membranes.Methods: A case control study involving women who delivered before 37 weeks gestation with and without inflammation of chorioamnion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…Herein, we showed that women who underwent spontaneous preterm labor with IAI had the highest amniotic fluid concentrations of extracellular ASC, which coincides with most elevated concentrations of IL-6 (ie, intra-amniotic inflammation). These results are consistent with previous studies, which demonstrated that amniotic fluid concentrations of caspase-1 33 (the predominant inflammasomeactivated caspase 46 ), IL-1β, 26 and IL-18 106 35,37,117 and that Ureaplasma species (genital mycoplasmas are the most common microorganisms found in women with IAI 12,16,[118][119][120][121][122][123] ) are capable of activating the inflammasome pathway in murine macrophages. 124 Together, these findings indicate that the inflammasome is involved in the mechanisms that lead to microbialassociated preterm labor and birth.…”
Section: Inflammasome Activation In Spontaneous Preterm Labor With supporting
confidence: 93%
“…Herein, we showed that women who underwent spontaneous preterm labor with IAI had the highest amniotic fluid concentrations of extracellular ASC, which coincides with most elevated concentrations of IL-6 (ie, intra-amniotic inflammation). These results are consistent with previous studies, which demonstrated that amniotic fluid concentrations of caspase-1 33 (the predominant inflammasomeactivated caspase 46 ), IL-1β, 26 and IL-18 106 35,37,117 and that Ureaplasma species (genital mycoplasmas are the most common microorganisms found in women with IAI 12,16,[118][119][120][121][122][123] ) are capable of activating the inflammasome pathway in murine macrophages. 124 Together, these findings indicate that the inflammasome is involved in the mechanisms that lead to microbialassociated preterm labor and birth.…”
Section: Inflammasome Activation In Spontaneous Preterm Labor With supporting
confidence: 93%
“…The presence of U. parvum in the placental tissue was found to be significantly associated with chorioamnionitis in a case–control study on women with preterm birth. It is also more prevalent among women who underwent delivery in their second trimester of pregnancy than in those who underwent delivery in their third trimester . A placenta infected with U. urealyticum also showed an association with a higher prevalence of preterm labor and pPROM …”
Section: Genital Ureaplasma Infection and Preterm Birthmentioning
confidence: 99%
“…Of the microorganisms associated with chorioamnionitis, the human Ureaplasma spp. are consistently identified as the most common microorganisms within the amniotic fluid and placentae of women with chorioamnionitis (1,62,123,133,134), funisitis (120,135,136), and preterm birth (1,137).…”
Section: Causative Agents Of Chorioamnionitismentioning
confidence: 99%